The Impact of Electricity Consumption and Economic Growth on the Electricity Lost in the Transmission and Distribution Processes in ASEAN - Nonthapot, Sakkarin; Jankanakittikul, Thanomsilp; Watchalaanun, Tanawat (International Journal of Energy Economics and Policy, 2025)
Electrical energy is one of the most important elements in human daily life. However, the amount of electricity production is limited. Therefore, the efficient use of electricity is one of the issues that needs to be considered, especially the loss of electricity from the distribution of energy to consumers. This study aims to compare the impact of electricity consumption and economic growth on electricity loss in the energy distribution process between countries located on the continent and islands of ASEAN member countries, which are 9 countries with the exception of Myanmar. This study employs data from 1990 to 2022 with Panel Autoregressive Distribution Lag (Panel ARDL). The results of the study show that in the long term, electricity consumption is a factor that triggers energy loss, both in continental and island countries. In addition, economic growth can only help to reduce energy loss by considering the overall picture and the island countries. In the Continental countries, electric power distribution systems should be developed continuously. While island countries, which may employ policies to stimulate the economy so that the public and private sectors generate enough income to develop an energy distribution system to better reduce losses from distribution.